Tinjauan Fiqh Muamalah Terhadap Strategi Marketing Pada Jual Beli Fashion di Kota Langsa - Khairuni Ishar; Muhazir (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2022)
Lottery prizes are one of the marketing strategies that are often used by merchants, this method is considered effective in attracting customers to come and shop. However, not a few lottery prizes that were carried out led to fraud which resulted in losses for customers. This paper aims to analyze the marketing strategies used by fashion traders in Langsa City. This paper is produced from an empirical study with a sociological approach. The object of research is the CB Fashion clothing business in Langsa City, the data collection method is in the form of interviews. The results of this study indicate that the marketing strategy used by CB Fashion Langsa with a lottery system with prizes applies to a minimum purchase with raffle prizes in the form of motorbikes and Umrah, of course this attracts customers because the prizes are given in large enough quantities, so that people are motivated to shop. In addition, the prize funds are not taken from the participant's dues but have been previously provided by the owner of CB Fashion Langsa.